2010
DOI: 10.1002/macp.201000561
|View full text |Cite
|
Sign up to set email alerts
|

Ni‐Catalyzed Polymerization of Poly(3‐alkoxythiophene)s

Abstract: The Ni-catalyzed polymerization of poly(3-alkoxythiophene)s (P3AOTs) was studied and compared with the controlled chain-growth polymerization of poly(3-alkylthiophene)s (P3ATs). By varying the ratio of the initial monomer concentration to the initiator concentration, no linear dependence of the molar mass was observed, revealing that the polymerization does not proceed via a controlled mechanism. This was also confirmed by analyzing the end-groups of the polymer with MALDI-TOF mass spectrometry. To acquire mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In another study, Van den Bergh et al investigated the KCTP of the ''reversed'' monomer 5-bromo-2-chloromagnesio-3-alkoxythiophene. [85] They observed polymerization in the presence of both Ni(dppp)Cl 2 and Ar-Ni(dppp)-Br. It is likely that a HH initiating dimer is possible here since the alkoxygroups are sterically less demanding than alkyl chains, as was already suggested earlier.…”
Section: Influence Of the Monomer Substitution Patternmentioning
confidence: 97%
“…In another study, Van den Bergh et al investigated the KCTP of the ''reversed'' monomer 5-bromo-2-chloromagnesio-3-alkoxythiophene. [85] They observed polymerization in the presence of both Ni(dppp)Cl 2 and Ar-Ni(dppp)-Br. It is likely that a HH initiating dimer is possible here since the alkoxygroups are sterically less demanding than alkyl chains, as was already suggested earlier.…”
Section: Influence Of the Monomer Substitution Patternmentioning
confidence: 97%
“…Especially for combinations of electron‐poor monomers and poor electron‐donating ligands, it is possible that the catalyst–polymer complex is not strong enough and dissociation of the catalyst from the polymer chain occurs prior to oxidative insertion . The catalyst can also dissociate from the polymer chain if the oxidative addition is too slow …”
Section: Introductionmentioning
confidence: 99%
“…A substituent ortho to the Ni‐bond slows down the reaction due to increased sterical hindrance, but is not a necessity for stability . It was also found that an alkoxy‐sidechain in the ortho ‐position hampers oxidative insertion due to its strong electron‐donating effect . Also, poly(fluorene)s, poly(cyclopentadithiophene)s, and poly(dithienosilole)s can all be polymerized in a living fashion, proving ortho ‐substituents are not necessary …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations